Nevidna srednjeveška Evropa Župa Bled - Pleterski, Andrej (ZRC SAZU, Založba ZRC, 2011)
If the term "prehistory" is used for the time and space not "seen" by written records, then there are "prehistoric" areas also in the time, which is generally considered "history". In this sense, there are still vast areas of Europe in the early medieval period, where the state of written records can be described as "prehistoric". It appears to be true especially for the regions settled by the Slavs. Among them is the area of the present-day Slovenia, where Bled lies. The latter does not "enter the history" before 1004.